Prevalence and health literacy on high blood pressure among late adulthood individuals in Northeast Thailand: a cross sectional study - Sornlorm, Kittipong; Glingasorn, Arunrat Puncha (Intelektual Pustaka Media Utama, 2025)
High blood pressure (HBP) is a leading risk factor for atherosclerotic cardiovascular disease and mortality. This study aimed to identify health literacy and other characteristics associated with HBP among late adults in Thailand. A cross-sectional study was conducted with 1,345 adults aged 35-59 years from Health Centers 7, 8, 9, and 10 in Northeast Thailand. Descriptive statistics and a generalized linear mixed model (GLMM) were used to determine the adjusted odds ratio (Adj. OR) and 95% confidence interval (CI). Results showed a prevalence of HBP at 24.76% (95% CI: 22.52-27.13). Multivariable analysis revealed a significant association between HBP and health literacy in finding health information (Adj. OR = 1.59, 95% CI: 1.28-1.96, p-value<0.001), as well as judging health information (Adj. OR = 1.34, 95% CI: 1.04-1.73, p-value=0.024). Additionally, history of smoking (Adj. OR=2.04, 95% CI: 1.29-3.24, p-value = 0.002), comorbidity (Adj. OR = 2.20, 95% CI: 1.76-2.74, p-value <0.001), physical activity (Adj. OR = 1.67, 95% CI: 1.28-2.16, p-value <0.001), and body mass index (Adj. OR = 2.21, 95% CI: 1.14-4.26, p-value=0.018) were found to be associated with HBP. Poor health literacy increases the risk of HBP. Relevant authorities must evaluate the group context and develop a suitable health literacy model.